Novel Applications of Gamma Irradiation on Fruit Processing - Colletti, Analia Cecilia; Denoya, Gabriela Inés; Vaudagna, Sergio Ramon; Polenta, Gustavo Alberto (Springer Nature, 2024)
Purpose of Review: Consumers increasingly demand for fruit products as a source of health-promoting compounds. However, fruits have a limited shelf life and their processing with thermal technologies significantly reduces their bioactive compounds. Instead, the application of a non-thermal technology like gamma irradiation could overcome this limitation. This review summarizes the latest research on the application of gamma irradiation on fruit processing. Recent Findings: Evidence shows that gamma irradiation produces positive effects on fruit products: fungal and microbial (spoilage and pathogenic) disinfection and decontamination, deparasitization, and delayed ripening and senescence, leading to a longer shelf life without affecting their quality. Besides, this technology is also being tested as a stress elicitor to induce physiological defense mechanisms in plant fruit tissues. Summary: The gamma irradiation process represents an opportunity to expand the export of value-added products over long distances, given its high efficiency to extend the shelf life of fruit products. Therefore, this paper provides a review of the currently available applications and effects of gamma irradiation in fruit processing. Considering the high cost associated to the refrigerated storage and transport of fruits, ionization is expected to give birth to a new era in the international trade of foods.